Reflexos da política nacional de inclusão escolar no Município-pólo de Vitória da Conquista/Bahia - Lago, Danúsia Cardoso (2010)
Municipal elementary schools receive most of the students from K 8th grade and the number of enrollments of students with special needs has increased nationwide as a result of the implementation of municipal policies for this area of education. Several studies about the inclusion of these students in municipal schools have been conducted with the purpose to evaluate the impact of the National Program for Inclusive Education: the right for diversity; evaluation of teacher training; understanding teachers concepts after the insertion of students with special needs in their classroom; and research on the general aspects related to the proposal of inclusion in the educational system. However, studies focusing on teachers concepts in relation to the proposal of inclusion, elaborated by the municipal office of education, are still insufficient to know the reality of more than a thousand Brazilians counties. Taking into consideration that the municipal board of education has the autonomy to elaborate such proposals whose implications are not yet thoroughly known the present study had the objective to analyze the inclusion in the context of a regional education network from the conceptions of teachers who have students with special needs in their classroom. The study was developed in the municipal school network of Vitória da Conquista, Bahia state (Brazil), more specifically in those schools with the largest number of students with special needs enrolled in regular classrooms. The methodological principle that guided this study was the qualitative approach. The research is descriptive in nature and data was collected in the field through questionnaires and semi-structured interviews. 30 municipal teachers who had students with special needs in their classrooms participated in the research. The interview script was evaluated by four judges and all interviews were recorded and later transcribed and submitted for content analysis. The results indicated hat even though the city of Vitória da Conquista is considered a regional educational center participating in the National Program of Inclusive Education since 2004, the increase in the number of enrollments of students with special needs is relatively recent; the results also show that most of these students have intellectual disability; teachers academic training is poor; the number of professionals qualified to offer services to students with special needs is small; also, lack of support to these teachers is pointed out as being one of the biggest obstacles to the realization of the inclusive education policies. It is expected that the positions and reflections of teacher participants can be seen as relevant sources for the City Board of Education - SMED, in the sense that the real educational needs of the network were found in these teacher reports. It is expected that the results bring new contributions to the process of school inclusion as well as a reflection on the pedagogical practices of the participating teachers regarding students with disabilities and that their conceptions can foster new guidelines that permeate the policies of educational inclusion of the municipality.